2023
DOI: 10.3390/nano13030454
|View full text |Cite
|
Sign up to set email alerts
|

Novel Synthesis of Nano Mg(OH)2 by Means of Hydrothermal Method with Different Surfactants

Abstract: Magnesium hydroxide (MOH) is a widely used inorganic chemical owing to its various properties. Hence, researchers have long studied its synthesis and its unique features. However, the morphological consequences have rarely been studied. Despite having several benefits for synthesizing nanoparticles, the hydrothermal method’s main drawbacks are its lengthy processing time and the high cost of raw materials. This research aimed to use more easily obtainable raw materials in a reasonably short time to synthesize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…In order to obtain fine particle dispersion in PU matrix, we used functionalized powder. MOH nanopowder (nMOH) was synthesized with the hydrothermal method which we investigated in a previous study with 75 nm plate particles [9]. However, the remainder of the raw materials were purchased from commercial companies whose characteristics are given in Table 1.…”
Section: Pu Composites Fabricationmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to obtain fine particle dispersion in PU matrix, we used functionalized powder. MOH nanopowder (nMOH) was synthesized with the hydrothermal method which we investigated in a previous study with 75 nm plate particles [9]. However, the remainder of the raw materials were purchased from commercial companies whose characteristics are given in Table 1.…”
Section: Pu Composites Fabricationmentioning
confidence: 99%
“…This was achieved by systematically loading a test zone, measuring the deformation, calculating the stress and strain based on the results, and using dumbbell-shaped samples with a length of 50 mm and a tensile testing equipment (ISO 37 standard, gauge length = 20 mm, strain rate = 10 mm/min). According to the FESEM images, nMOH which was studied in another paper [9], has a vertical orientation and plate shape. The mMOH presents agglomerated micron particles, but SO was formed in a spherical shape.…”
Section: Pu Composite Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies, the results of which are reported by F. Nisa et al [6] (on the use of nano-MgO biosynthesis technology), M. Kotresh et al [7] (on the temperature regimes of production of nanosize magnesium oxide), Z. Rajabimashhadi et al [8] (on the use of hydrothermal methods for the production of magnesium oxide nanoparticles) in the review parts contain generalisations about the existence of a fairly wide range of technological methods for the production and synthesis of the target nanomaterial, which mostly bear signs of laboratory-scale production and do not form ideas about the generalised optimised technology for the production of nanosize magnesium oxide for industry (except for individual proposals in the form of publications by F. Mirza and H. Makwana [9], in which the co-precipitation method is preferred). Also noteworthy are the studies by J. Veronica et al [10] (which favours the sol-gel method), S. Abinaya et al [11] (which favours the green synthesis method), which in general do not form a stable and consistent vector of commitment to any one prevailing method of producing the target nanoproduct).…”
Section: Introductionmentioning
confidence: 99%